Iowa Birdline update, December 25, 1989 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1989)
Notes for the Iowa Birdline update for December 25, 1989. Highlights include Prairie Falcons, a Snowy Owl and the continued presence of Townsend's Solitaires and Eurasian Tree Sparrows. Epson - sheet feed/flatbed